Removing Barriers to Library Development in Ghana - Alemna, A.A. (Ghana Library Journal, 1997)
The topic "Removing Barriers to Library Development in Ghana," presupposes that there are some barriers to library development in the country. And indeed, there are barriers. Fortunately for me, some of the barriers are in the sub-themes for this Congress. This makes my work easier, because specialists in these areas are going to dilate on these issues. All the same, I shall touch on a few of the barriers that have not been highlighted in the sub-themes and then attempt to provide ways of removing the barriers.